Ecosystem services of poplar at long‐term phytoremediation sites in the Midwest and Southeast, United States. Issue 6 (18th June 2019) - Zalesny, Ronald S.; Headlee, William L.; Gopalakrishnan, Gayathri; Bauer, Edmund O.; Hall, Richard B.; Hazel, Dennis W.; Isebrands, Jud G.; Licht, Louis A.; Negri, M. Cristina; Nichols, Elizabeth Guthrie; Rockwood, Donald L.; Wiese, Adam H.
Abstract: Short rotation woody crops (SRWCs) including Populus species and their hybrids (i.e., poplars) are ideal for incorporating biomass production with phytotechnologies such as phytoremediation. To integrate these applications, 15 poplar plantings from nine long‐term phytoremediation installations were sampled from 2012 to 2013 in the Midwest (Illinois, Iowa, Wisconsin) and Southeast (Alabama, Florida, North Carolina) United States. In this review, we report summary results of this sampling and how performance at each site compared with comparable phytoremediation systems in the literature. We review significant genotypic differences from each planting within the context of provisioning (i.e., biomass production) and regulating (i.e., carbon sequestration) ecosystem services and how they relate to the need for a cleaner environment during times of accelerated ecological degradation. Overall, the contaminated poplar sites provided these ecosystem services comparable to noncontaminated poplar sites used for bioenergy and biofuels feedstock production. For example, phytoremediation trees at the Midwestern sites had biomass values ranging from 4.4 to 15.5 Mg ha −1 y −1, which was ~20% less relative to bioenergy trees ( p = .0938). Results were similar for diameter and carbon, with some genotype × environment interactions resulting in phytoremediation trees exhibiting substantially greater growth and productivity (i.e., +131% at one site). As illustrated in the current review, phytoremediation success can be increased with the identification and deployment of genotypes tailored to grow well and tolerate a broad diversity of contaminants (generalists) (i.e., 'DN34', 'NM6', '7300501') versus those that significantly outperform their counterparts under unique site conditions (specialists) (i.e., '220‐5', '51‐5', 'S13C20'). This article is categorized under: Concentrating Solar Power > Climate and Environment Bioenergy > Economics and Policy Bioenergy > Science and Materials Abstract : Least‐squares means of mean annual increment (MAI) of aboveground total (stem + branch) dry biomass and MAI of aboveground total carbon for 15 poplar clones evaluated at an industrial brownfield in Panama City, FL (planting H1). With the exception of 'DN21' and 'DN31' that are both Populus deltoides × P. nigra F1 hybrids, all clones belong to the P. deltoides genomic group. Different letters above bars within a trait represent statistically significant differences ( p < .05). Error bars equal one standard error of the mean.